Reduced expression of the presynaptic co-chaperone cysteine string protein alpha (CSPα) does not exacerbate experimentally-induced ME7 prion disease. (4th March 2015) - Davies, Matthew J.; Cooper, Matthew; Perry, V. Hugh; O'Connor, Vincent
Highlights: CSPα is reduced in ME7-animals during disease progression. CSPα heterozygosity does not accelerate behavioural changes in ME7-animals. Prion disease pathology is not altered by reduced CSPα expression. Abstract: Infection of mice with the ME7 prion agent results in well-characterised neuropathological changes, which includes vacuolation, neurodegeneration and synaptic degeneration. Presynaptic dysfunction and degeneration is apparent through the progressive reduction in synaptic vesicle proteins and eventual loss of synapses. Cysteine string protein alpha (CSPα), which regulates refolding pathways at the synapse, exhibits an early decline during chronic neurodegeneration implicating it as a mediator of disease mechanisms. CSPα null mice develop a progressive neuronal dysfunction through disruption of the integrity of presynaptic function. In this study, we investigated whether reduced expression of CSPα would exacerbate ME7 prion disease. Wild type (+/+) and heterozygous (+/−) mice, which express about a ∼50% reduction in CSPα, were used as a distinct genetic background on which to impose prion disease. +/+ and +/ − mice were inoculated with brain homogenate from either a normal mouse brain (NBH) or from the brain of a mouse which displayed clinical signs of prion disease (ME7). Behavioural tests, western blotting and immunohistochemistry, which resolve key elements of synaptic dysfunction, were used to assess the effect of reduced CSPα on disease. Behavioural tests revealed no change in the progression of disease in ME7–CSPα +/− animals compared to ME7–CSPα +/+ animals. In addition, the accumulation of misfolded PrP Sc, the diseased associated gliosis or synaptic loss were not different. Thus, the misfolding events that generate synaptic dysfunction and lead to synaptic loss are unlikely to be mediated by a disease associated decrease in the refolding pathways associated with CSPα.